Pengembangan Bahan Ajar E-LKDP Berbasis Hots (Higher Order Thinking Skills) pada Mata Pelajaran Akuntansi Keuangan Kelas XI Akuntansi untuk SMK Negeri di Surabaya - Siti Tasriah; Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Technological advances and current industrial needs require students to adapt. Students are required to have 4C skills (critical, creative, communicative, collaborative). Critical reasoning skills are one of the abilities that vocational school level students are expected to master, which directs their graduates to be able to meet the needs of the business and industrial world. This research aims to develop teaching materials in the form of E-LKPD based on HOTS (Higher Order Thinking Skills) using a flip PDF display which consists of activities to train students' critical reasoning skills. This research uses the 4D development model (define, design, develop, disseminate) from Thiagarajan which was carried out until the development stage due to researcher limitations. The result of this development research is that the HOTS-based E-LKPD obtained an average validation score from experts of 86.88% which is categorized as very feasible. Meanwhile, the results of trials on students in class XI Accounting at State Vocational Schools in Surabaya obtained an average percentage of 96.3% which was interpreted as very good.